2008
DOI: 10.1103/physrevb.77.014501
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nonequilibrium quasiparticles in narrow-gap superconducting tunnel junctions

Abstract: The latest generation of high quality, narrow gap, superconducting tunnel junctions ͑STJs͒ exhibits a steadystate and time-dependent behavior which cannot be described satisfactorily by previous treatments of nonequilibrium quasiparticle ͑qp͒ dynamics. These effects are particularly evident in experiments using STJs as detectors of photons, over the range from near infrared to x ray. In this paper, we present a detailed theoretical analysis of the spectral and temporal evolution of the nonequilibrium qp and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…The smaller exponent for QP trapping on a discrete state has an important implication for nonequilibrium effects in multiple tunneling superconducting tunnel junctions ͑STJs͒. 16,17 In order to estimate the order of magnitude of the continuum-bound trapping rate, we consider Ta as a typical superconductor. Assuming the presence of Kondo impurities with a discrete state residing deep inside the gap, we will take for an estimate ⑀ 0 =1/ 2⌬.…”
Section: B Continuum-bound Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller exponent for QP trapping on a discrete state has an important implication for nonequilibrium effects in multiple tunneling superconducting tunnel junctions ͑STJs͒. 16,17 In order to estimate the order of magnitude of the continuum-bound trapping rate, we consider Ta as a typical superconductor. Assuming the presence of Kondo impurities with a discrete state residing deep inside the gap, we will take for an estimate ⑀ 0 =1/ 2⌬.…”
Section: B Continuum-bound Trappingmentioning
confidence: 99%
“…However, the decrease in pair-breaking efficiency for sub-2⌬ phonons may be partially compensated by their longer escape time, which occurs because phonons escape from an acoustically softer superconductor into a rigid dielectric substrate is constrained to lie within the critical escape cone defined by the critical incidence angle for the superconductor-substrate interface. 16 Thus the process of phonon scattering from outside to inside the critical cone becomes crucial; in general, this conversion is less efficient for lower-energy phonons. Nevertheless despite the extra complications discussed above, impurity enhanced recombination is the principal recombination channel at the lowest temperatures because of the much higher occupation numbers for the impurity bound states.…”
Section: Continuum-bound Recombinationmentioning
confidence: 99%
“…Finally localized microscopic states associated with magnetic moments, either in the bulk or at the surface, are known to exist inside the gap region [33]. Modelling of STJ responsivity and signal decay time as a function of temperature and photon energy made it possible to determine local trap densities and their levels [20,27] (Figs. 6 and 7) give typical results.…”
Section: Local Trap Modelmentioning
confidence: 99%
“…Previous results 15 on STJs have indicated that quasiparticle losses inside the STJ are due to bulk material losses and a concentration of loss centers near the leads, especially the plugs which are made of higher gap material to avoid outdiffusion of quasiparticles. Recent developments have indicated that quasiparticle losses in superconducting materials may be due to a very small amount of magnetic impurities in the high grade superconducting material.…”
Section: -8mentioning
confidence: 99%
“…This process, denoted by the relaxation rate ␥ s ͑i͒ , depends on the STJ proximisation and can be calculated. 15 Due to sequential tunnelling quasiparticles gain energy, equal to twice the applied bias voltage ͑2 eV b ͒ with each tunnelling cycle, and after a sufficient number of cycles without relaxation the quasiparticles are promoted from group 3 into group 2. The number of tunnels needed to reach an energy above the energy gap of the absorber and thus to change the trapping efficiency can be adjusted for a given STJ lay-out with the bias voltage.…”
Section: Modeling Of Droid Responsementioning
confidence: 99%